Multilayer Periodic and Random Metamaterial Structures: Analysis and Applications - Rola Aylo; Georges Nehmetallah; Han Li; Partha P. Banerjee (IEEE Access, 2014)
In recent years, multilayer photonic bandgap structures comprising stacks of alternating layers of positive and negative index have been proposed for a variety of applications, such as perfect imaging, filters, sensors, coatings for tailored emittance, absorptance, etc. Following a brief review of the history of negative index materials, the performance of such stacks is reviewed, with emphasis on analysis of plane wave and beam propagation, and possible applications in sensing. First, the use of the transfer matrix method to analyze plane wave propagation in such structures to determine the transmittance and reflectance is developed. Examples of cases where the Bragg bandgap and the so-called zero <;\(n \) > gap can be used for possible applications in sensing are illustrated. Next, the transfer matrix approach is extended to simulate the spatial evolution of a collection of propagating and nonpropagating TE and TM plane waves (or plane wave spectra) incident on such multilayer structures. The use of the complex Poynting theorem in checking the computations, as well as monitoring powers and the stored electric or magnetic energy in any section of the multilayer stack, is illustrated, along with its use in designing alternating positive and negative index structures with optimal gain to compensate for losses in the negative index material. Finally, the robustness of PIM-NIM stacks with respect to randomness in the dimensions of the PIM-NIM structure is examined. This should be useful in determining the performance of such structures when they are physically fabricated.